Study on the erosion mechanism of acid coal slag interactions with silicon carbide materials in the simulated atmosphere of a coal gasifier. Issue 5 (1st April 2017) - Cai, Binli; Li, Hongxia; Zhao, Shixian; Sun, Honggang; Li, Pengtao; Yan, Shuangzhi; Wan, Longgang; Wang, Gang; Cao, Zhanmin
Abstract: In this paper, the dynamic erosion of silicon carbide interaction with acid coal slag was studied in an improved rotary drum furnace under the simulated conditions of a slagging gasifier at temperature of 1500 °C. Microstructures of corroded samples were observed by SEM, and the erosion mechanism was investigated by thermodynamic simulation based on SEM analysis. This revealed that SiC reacted with FeO to form a Si-Fe-C alloy on the sample surface, and the active oxidation of SiC was conducted in the experimental atmosphere. Furthermore, SiO2 (s), SiO(g), CO(g), and CO2 (g) were formed. Finally, SiO2 dissolved in the molten slag, and SiO(g), CO(g), and CO2 (g) spread continuously. The pore structures on were altered by the oxidation reaction, which facilitated slag penetration into the samples through the pores to form a thin reaction layer.